Bipolar Disorder in Statehood: is China “Dr. Jekyll” or “Mr. Hyde” or Both? - Jones, David A. (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
American and Chinese interests seem to be at one time in agreement and at another at loggerheads over issues that involve armed services, diplomacy, economics, human rights, intelligence, trade and culture. Part of what may appear to be a growing déracinement, or mutual disenchantment, arising from diverse viewpoints over infrastructure development globally but especially in sensitive developing areas such as the stand-off in the South China Sea and elsewhere along the Pacific coastline of Southeast Asia, and the Western Pacific Rim. China seems to be reconstructing its ancient feudal empire, actual or imaginary, in the territory to its South, the ASEAN bloc. This article will address some issues of compatibility and conflict that unite China but that sometimes divide it from the United States and the West, then assesses what alternative strategies should be adopted or abandoned in the interests of global and regional harmony coupled with security. It urges greater cooperation and collaboration, a development of a code of conduct for state behavior in the Indo-Asia-Pacific region, together with a concerted East–West effort to maintain a stable economy for China and a sustainable trade relationship between China, Europe, and North America.